The System of Profound Knowledge – Answer to the Challenges of the XXI Century (Global Journal of Human-Social Science, 2023)
In this work the question of how the main principles of good management in the XXI century should look like is being discussed In other words what are the key features of management that relate to the main challenges of our time In the author s view the answer to these questions was given by William Edwards Deming WED in 1993 when his book The New Economics was published Deming 1993 This answer has a well-known name The System of Profound Knowledge SoPK It consists of four interrelated components appreciation for a system knowledge of variation theory of knowledge and psychology It is argued that the principles of the SoPK comprise the most essential facets of that type of management which society needs the most Unfortunately few amount of people are familiar with the concept of the SoPK and even fewer number of managers use it in their work In my view WED s ideas are worth being taught in the primary education curriculum The understanding of the SoPK should be included into people s common sense as their ability to read and to write